Application of Bethesda system for conventional cervical cytology: a study of 340 cases - Valiya, Lalji G.; Baxi, Seema N. (International Journal of Research in Medical Sciences, 2017)
Background: Cervical carcinoma is an important women’s health problem worldwide. The Bethesda system is a complete diagnostic system that recognizes the cytopathology report as a medical consultation. The aim of this study is to evaluate the abnormal cytological entities detected by cervical Pap smear, to classify the cytological findings according to the recently recommended Bethesda system and to discuss the significance of Pap smears screening programs. Methods: A prospective study on conventional cervical cytology was performed including 340 women, 111 postmenopausal and 229 reproductive age group, attending the Gynaecologic out-patient department at a tertiary care hospital in Bhavnagar district of Gujarat state. Cytological findings including incidence of unsatisfactory smears, inflammatory smears and epithelial abnormalities were classified according to the Bethesda system 2001. Results: Overall incidence of unsatisfactory smears was 9.4%, of squamous cell abnormality was 4.1% and of glandular cell abnormality was 1.2%. Highest frequency of epithelial cell abnormalities (squamous as well as glandular) was seen in 61-70 years age-group women (35.71%) and in women presented with complaints of post-menopausal bleeding (22.5%). Conclusions: The study had shown a relatively low prevalence of epithelial abnormalities in cervical smears. The 2001 Bethesda system seems to reduce the number of cervical smear diagnoses of Atypical Squamous Cells (ASC), without causing any impairment in the diagnosis of High grade Squamous Intraepithelial Lesion (HSIL) thus decreasing the number of unnecessary interventions.